An Alkaline Slurry Design for Co-Cu CMP Systems Evaluated in the Tribo-Electrochemical Approach. (1st January 2018) - Johnson, C. A.; Wei, S.; Roy, D.
Abstract : The sub-14 nm technology nodes of integrated circuits require metal components of ultrathin linewidths. The chemical mechanical planarization (CMP) protocols needed to process such structures are associated with several challenges, one of which is to design/screen slurry formulations required to address both the scaling and the nontraditional metal chemistries of these structures. Laboratory scale tribo-electrochemical techniques serve as a cost-effective yet comprehensive means to aid these tasks, and the present work focuses on further quantifying this approach with an alkaline slurry formulation designed to planarize Co diffusion barriers for Cu lines. The CMP strategy uses controlled corrosion in a (potentially abrasive-free) slurry of potassium acetate, hydrogen peroxide, and benzotriazole. The tribo-electrochemical experiments involve open circuit potential transients, current interruption, and potentiodynamic polarization. Material removal rates, normalized with respect to the polisher parameters are analyzed as specific wear rates to quantitatively probe the chemical aspects of CMP. The slurry functions necessary to control galvanic corrosion and CMP selectivity of Co are investigated. The necessity for incorporating tribo-control in these measurements is demonstrated by showing how the results obtained with stationary metal samples could result in misleading conclusions about the galvanic corrosion rates.